2016
DOI: 10.1021/jacs.6b08705
|View full text |Cite
|
Sign up to set email alerts
|

C–H Activation on Co,O Sites: Isolated Surface Sites versus Molecular Analogs

Abstract: The activation and conversion of hydrocarbons is one of the most important challenges in chemistry. Transition-metal ions (V, Cr, Fe, Co, etc.) isolated on silica surfaces are known to catalyze such processes. The mechanisms of these processes are currently unknown but are thought to involve C-H activation as the rate-determining step. Here, we synthesize well-defined Co(II) ions on a silica surface using a metal siloxide precursor followed by thermal treatment under vacuum at 500 °C. We show that these isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
141
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 131 publications
(155 citation statements)
references
References 99 publications
10
141
0
4
Order By: Relevance
“…[37] At 300°C, one weak peak at 1580 cm À 1 appeared which belongs to the carbonaceous products. [39] As reported previously by many studies in the presence of hydrocarbons, the peaks observed between 1585-1560 cm À 1 belongs to carbonaceous products [38] Furthermore, upon switching propane with He gas at 550°C (Figure 10(c)), the bands at 2967 and 1370 cm À 1 disappeared and a broad peak at 1585 cm À 1 still appeared.…”
Section: In-situ Drifts Analysis For Co/al 2 O 3 à Ns Catalystsupporting
confidence: 66%
“…[37] At 300°C, one weak peak at 1580 cm À 1 appeared which belongs to the carbonaceous products. [39] As reported previously by many studies in the presence of hydrocarbons, the peaks observed between 1585-1560 cm À 1 belongs to carbonaceous products [38] Furthermore, upon switching propane with He gas at 550°C (Figure 10(c)), the bands at 2967 and 1370 cm À 1 disappeared and a broad peak at 1585 cm À 1 still appeared.…”
Section: In-situ Drifts Analysis For Co/al 2 O 3 à Ns Catalystsupporting
confidence: 66%
“…[89] Calculations performed on Cr III /SiO 2 also suggest that b-alkyl elimination from an M-propyl intermediate can lead to ethylene and methane-the cracking products. [89,91,93,94,96] Para-hydrogeninduced polarization (PHIP) experiments for Cr and Co have indicated that p-H 2 could be incorporated into propene in ap airwise fashion, consistent with the hydrogenation and dehydrogenation involving heterolytic H À Ha nd C À Hs plitting at an M À O site. [89,91,93,94,96] Para-hydrogeninduced polarization (PHIP) experiments for Cr and Co have indicated that p-H 2 could be incorporated into propene in ap airwise fashion, consistent with the hydrogenation and dehydrogenation involving heterolytic H À Ha nd C À Hs plitting at an M À O site.…”
Section: Non-oxidative Dehydrogenationmentioning
confidence: 72%
“…[88,89] Achromium aluminate material free of surface Si sites, Cr-2/Al 2 O 3 ,has also been prepared by the grafting of Cr(k 2 -Al(OiPr) 4 ) 3 (Cr-2)o nto Al 2 O 3-700 followed by thermal treatment at 400 8 8C( Scheme 2d). [89] Similarly,monomeric Ga III [90] and Co II [91] sites supported on silica have also been prepared by using this approach (Scheme 2). Thep resence of monomeric sites was established through av ariety of spectroscopic techniques,i ncluding aW avelet transform analysis of the EXAFS data.…”
Section: Non-oxidative Dehydrogenationmentioning
confidence: 99%
See 2 more Smart Citations